Compact 999.6 nm Actively Q-Switched Yb3+:LuAlO for Laser-Induced Breakdown Spectroscopy Laser - A. Rudenkov; V. Kisel; A. Yasukevich; K. Hovhannesyan; A. Petrosyan; N. Kuleshov (Приборы и методы измерений)
Compact actively Q-switched diode-pumped lasers based on Yb3+-materials are of practical importance for wide range of scientific, industrial and biomedical applications. The aim of this work was to study the Yb3+:LuAlO3 actively Q-switched laser.One of the most promising crystalline hosts for rare-earth ions are Perovskite-like aluminate crystals. Yttrium aluminate crystal YAlO3 (YAP) is a well-known host with good thermal and mechanical properties (thermal conductivity for undoped crystal is about 11 W/m·K and about 8 W/m·K for Yb(5 at.%):YAP) similar to those of YAG. The reduction in the thermal conductivity of doped laser crystal in comparison with host materials is small in the case of ions with close atomic mass and ionic radii such as for Yb3+ and Lu3+. This feature makes LuAlO3 (LuAP) more promising host crystal for doping by Yb3+ ions in contrast to YAP especially for high output power laser systems. In our work, for the first time to the best of our knowledge actively Q-switching laser operation of Yb3+:LuAP single crystal was demonstrated. The maximum average output power of 4.9 W at 50 kHz pulse repetition frequency (PRF) with opt.-to-opt. efficiency of 21 % was obtained with 30 % OC transmittance. Output power as high as 3.3 W with 333 µJ-laser pulses with duration of about 11.5 ns was demonstrated at 10 kHz PRF the corresponding pulse peak power was 29 kW. 97 µJ second harmonic pulses obtained with 29 % conversion efficiency at 10 kHz PRF.Performed investigations show high potential of Yb3+:LuAP crystals as active elements of compact diode pumped actively Q-switched lasers due to high stimulated emission cross-section (≈ 3.74·10-20 cm2) at 999.6 nm wavelength and significant reduction of heat load on the active element when pumping around 980 nm and generation around 999 nm.